RANCANG BANGUN APLIKASI PENYEWAAN MOBIL ONLINE “EAZYRENT” BERBASIS WEBSITE - Geasela, Yemima Monica; Lijadi, Trinity; Tanria, Devi; Drisella, Tiffany; Dagara, Brithany Russel (Infotech: Journal of Technology Information, 2023)
The world of technology is now more advanced and sophisticated, where technological developments are widely used to facilitate and support people in carrying out their every activity. Many activities and jobs are impacted by technological advances, one of which is in the world of rental. Car rental is a business entity in the field of four-wheeled vehicle rental services. This study aims to provide complete information to make it easier for users to use it, as well as build a car rental information system on the website so that car rental transactions and promotions can be carried out online and save users more time when it comes to car rentals without the need to come to the rental office in person. because in this day and age where technology is rapidly developing it changes the lifestyle of people who want a simple, easy-to-understand, quick-to-access, flexible, and efficient system that can be accessed anywhere. The purpose of this research is to build a web-based car rental information system on Eazyrent, with research boundaries that will include the process of entering car data, tenant data, and user data. This research was conducted using the waterfall model. It consists of several stages starting with a literature study, followed by determining the formulation of the problem, then analyzing the data that has been collected, discussing the research results in the form of dataflow such as decomposition diagrams, context diagrams, system pages, and testing. After discussing the results, the study was closed with conclusions and suggestions. The results of this study can be concluded that by building an information system it can become a liaison between tenants and Eazyrent users, and can accommodate all the data information needed by users when using Eazyrent, so that it makes it easier for users.